課程實施在推廣中的意涵與革新體現：課程史觀點 Curriculum Implementation Implies the Meanings of the Dissemination and Innovation: The Viewpoint of Curriculum History - 侯一欣 Yi-Hsin Hou; 高新建 Shin-Jiann Gau (National Taiwan Normal University, 2018)
本研究以歷史回顧的文獻分析技術就過程、觀點爬梳相關名詞釋義，並整合課程革新實施模式的探討，從中瞭解課程革新實施的相關詞義生成與脈絡演變，作為國內課程實施的學術和實務參考之借鏡。本研究的主要發現臚列如下：一、起源於美國 1960 年代推廣課程革新的失敗，「課程實施」的術語乃從「課程推廣」做概念衍伸。又因 Fullan 實施階段的劃分並不嚴謹，「課程實施」若附屬於「課程推廣」的子過程，則實施、擴散和制度化或可望做進一步 的理論整合。二、課程革新實施的觀點從忠實轉變為調適取向，目標與結構逐漸消融，外來革新結合在地文化深耕，乃能導致後續的人際擴散與制度化。三、課程革新實施的模式主要為「自上而下」及「由下而上」兩種類型，各種模式的發展有其脈絡背景及假定基礎。 The aim of this study was to analyze previous literature on academics for integrating the model and process of innovative curriculum implementation (ICI). The findings yielded the following conclusions: (1) The academic term ICI was derived on the basis of curriculum dissemination and related factors and originated from a failure in curriculum innovation in the United States during the 1960s. The academic error committed by Fullan caused the integration of diffusion and institutionalism as a combined theory. (2) The concept of ICI was revised from fidelity to mutual adaptation. Moreover, the concept does not emphasize the goal and structure of ICI but combines innovation with culture to enable interpersonal diffusion and institutionalization. (3) The model of ICI differs from the top-down and bottom-up approaches, all of which were developed on the basis of assumptions.